Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(A=\left(a-2b+c\right)-\left(a-2b-c\right)\)
\(A=a-2b+c-a+2b+c=2c\)
b) \(B=\left(-x-y+3\right)-\left(-x+2-y\right)\)
\(B=-x-y+3+x-2+y=1\)
c) \(C=2\left(3a+b-1\right)-3\left(2a+b-2\right)\)
\(C=6a+2b-2-6a-3b+6=4-b\)
a. \(A=\left(a-2b+c\right)-\left(a-2b-c\right)=a-2b+c-a+2b+c=0\)
b. \(B=\left(-x-y+3\right)-\left(-x+2-y\right)=-x-y+3+x-2+y=1\)
c. \(C=2\left(3a+b-1\right)-3\left(2a+b-2\right)=6a+2b-2-6b-3b+6=4-3b\)
a) (m - n) (m + n) = m2 + mn - mn + n2 = m2 + n2
b) x(a - b) - x(a + b) = ax - bx - ax - bx = -2bx
c) (a2 - ax + by) - (by - a2 - ax) = a2 - ax + by - by + a2 + ax = 2a2
d) (a - b) (a + b) - (b - a)b = a2 + ab - ab - b2 - b2 + ab = a2 - 2b2 + ab
x=by+cz;y=ax+cz;z=ax+by
=>x+y+z=2(ax+by+cz)
\(\Leftrightarrow\frac{x+y+z}{2}=ax+by+cz\)
\(\Leftrightarrow y+z=\frac{x+y+z}{2}+ax;z+x=\frac{x+y+z}{2}+by;x+y=\frac{x+y+z}{2}+cz\)
\(\Leftrightarrow\frac{y+z-x}{2}=ax;\frac{z+x-y}{2}=by;\frac{x+y-z}{2}=cz\)
\(\Leftrightarrow\frac{y+z-x}{2x}=a;\frac{z+x-y}{2y}=b;\frac{x+y-z}{2z}=c\)
\(\Rightarrow A=\frac{1}{1+\frac{x+y-z}{2z}}+\frac{1}{1+\frac{y+z-x}{2x}}+\frac{1}{1+\frac{z+x-y}{2y}}=\frac{1}{\frac{x+y+z}{2x}}+\frac{1}{\frac{x+y+z}{2y}}+\frac{1}{\frac{x+y+z}{2z}}\)
\(=\frac{2x}{x+y+z}+\frac{2y}{x+y+z}+\frac{2z}{x+y+z}=\frac{2\left(x+y+z\right)}{x+y+z}=2\)
1. a, 3x + 2 \(⋮2x-1\)
Có 3(2x - 1) \(⋮2x-1\)
Và 2(3x - 2) \(⋮2x-1\)
=> 6x - 4 - 6x + 3 \(⋮2x-1\)
<=> -1 \(⋮2x-1\)
=> 2x - 1 \(\inƯ\left(1\right)=\left\{\pm1\right\}\)
=> 2x = 2; 0
=> x = 1; 0 (thỏa mãn)
@Lớp 6B Đoàn Kết
1. b, x2 - 2x + 3 \(⋮x-1\)
<=> x(x - 2) + 3 \(⋮x-1\)
<=> x(x - 1) - x + 3 \(⋮x-1\)
<=> x(x - 1) - (x - 1) - 2 \(⋮x-1\)
<=> (x - 1)2 - 2 \(⋮x-1\)
<=> -2 \(⋮x-1\)
=> x - 1 \(\inƯ\left(2\right)=\left\{\pm1;\pm2\right\}\)
=> x = 2; 0; 3; -1 (thỏa mãn)
@Lớp 6B Đoàn Kết
\(\left(a-b\right)\left(a^2+ab+b^2\right)=a^3+a^2b+ab^2-ba^2-ab^2+b^3=a^3+b^3\)
Lời giải:
a)
$x(a-b)-x(a+b)=xa-xb-xa-xb=-2xb$
b)
$(a^2-ax+by)-(by-a^2-ax)=a^2-ax+by-by+a^2+ax=2a^2$
c)
$(a-b)(a+b)-(b-a)b=a^2-b^2-(b^2-ab)=a^2-b^2-b^2+ab=a^2-2b^2+ab$
\(a,x\left(a-b\right)-x\left(a+b\right)\)
\(=ax-bx-ax-bx=-2bx\)
\(b,\left(a^2-ax+by\right)-\left(by-a^2-ax\right)\)
\(=a^2-ax+by-by+a^2+ax=2a^2\)
\(c,\left(a-b\right)\left(a+b\right)-\left(b-a\right).b\)
\(=a^2-b^2-b^2+ab\)
\(=\left(a-b\right)^2-b^2=\left(a-b-b\right)\left(a-b+b\right)\)
\(=\left(a-2b\right).a\)